Analisis Efektivitas Dan Kontribusi Pajak Mineral Bukan Logam Dan Batuan Dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Tanjung Jabung Timur - Usdeldi Usdeldi; Atar Satria Fikri; Ika Jasuma Putri (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2024)
This study aims to determine how the effectiveness and contribution of Non-Metal and Rock Minerals tax in increasing the PAD of East Tanjung Jabung Regency, as well as knowing the obstacles in the PMBLB collection process. This research was conducted in Bakeuda, East Tanjung Jabung Regency in the 2018-2022 period. This research uses Quantitative Descriptive method. The data in this study is in the form of targets and realization of PMBLB in 2018-2022 as well as targets and realization of Regional Tax revenues of East Tanjung Jabung Regency in 2018-2022. The percentage of effectiveness rate and contribution of PMBLB is calculated using the effectiveness and contribution ratio formula. The results showed that from 2018-2022 the target and realization of PMBLB experienced instability with varying levels of effectiveness and contribution. The highest effectiveness rate of PMBLB acceptance occurred in 2021 at 58.19% with ineffective criteria and the lowest in 2020 at 22.21% with ineffective. The level of PMBLB's contribution in increasing PAD is still very lacking, during 2018-2022 with an average contribution of 0.71%. Obstacles in the PMBLB collection process include lack of taxpayer awareness, the number of miners who do not have permits, and lack of human resources in Bakeuda, East Tanjung Jabung Regency.